Um alerta de tempestade: modernismo e romantismo no retrato do Brasil - Merlo, Hugo Ricardo (2017)
This is a study on the Modernism and Romanticism on Retrato do Brazil (1928), by Paulo Prado. Our main objective consists in contributing to the studies of the relation between the multiple experiences of the modernism in Brazil and the Brazilian historiography. We aim to do that through studying: 1) the presence, in Retrato do Brasil, of a strong preoccupation with the Brazilian formation; 2) its form of a historical essay and the author’s intent of producing a synthesis of the Brazilian history; 3) Paulo Prado’s interpretation of the importance of the Romanticism to the constitution of the Brazilian nationality; and, lastly, 4) the reception of the work in the months that followed its publication. We expect to demonstrate that this relation between modernisms and historiography resignifies the mechanisms of legitimation of historical works during the first decades of the XXth century, in Brazil, and that they also result into the constitution of new layers of temporality and of a regime of historiographical production based upon the notion of formation.